USING GRAPHIC ORGANIZERS TO IMPROVE READING COMPREHENSION SKILL THROUGH JIGSAW ACTIVITY - Astuti, Dwi; Regina, Regina; Yuliana, Yohanes Gatot Sutapa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractGraphic organizer strategy is a strategy commonly used in reading class to improve students’ understanding toward texts. This strategy has been deemed as effective across level of students and schools. Yet previous studies on graphic organizer has exclusively brought this strategy in to the classroom on the basis of individual work. Little is known how teachers may as well experience success if they combine the strategy with a collaborative learning model. Addressing this gap this study examined the effects of graphic organizer strategy when it is combined with a collaborative learning model called jigsaw activity on behavior and student’s understanding on text. The participant of this study were thirty tenth-grade students of Audio-Video Technique Class in SMKN 2 Pontianak in academic year 2017/2018. From the data which was collected both qualitatively and quantitatively it can be concluded that there were improvement on students’ behavior indicated by they were being active and collaborative during the implementation of the strategy in the classroom. The result of reading test also suggested that the students’ achievement on reading comprehension improved after they made use graphic organizer as concept map activities during reading. Keywords : Graphic Organizer, Jigsaw Activity, Reading Comprehension, Student’s Behavior